Facioscapulohumeral muscular dystrophy region gene-1 (FRG-1) is an actin-bundling protein associated with muscle-attachment sites - Liu, Qian (Company of Biologists, 2010)
In vertebrates, overexpression of facioscapulohumeral muscular dystrophy (FSHD) region gene 1 (FRG1) recapitulates the pathophysiology exhibited by FSHD patients, although the role of FRG1 in FSHD remains controversial and no precise function for FRG1 has been described in any organism. To gain insight into the function and potential role of FRG1 in FSHD, we analyzed the highly conserved Caenorhabditis elegans ortholog, frg-1. C. elegans body-wall muscles contain two distinct subcellular pools of FRG-1: nuclear FRG-1, concentrated in the nucleoli; and cytoplasmic FRG-1, associated with the Z-disk and costamere-like structures known as dense bodies. Functionally, we demonstrate that FRG-1 is an F-actin-bundling protein, consistent with its localization to dense bodies; this activity is conserved in human FRG1. This is particularly intriguing because it places FRG-1 along side the list of dense-body components whose vertebrate orthologs are involved in the myriad myopathies associated with disrupted costameres and Z-disks. Interestingly, overexpressed FRG-1 preferentially accumulates in the nucleus and, when overexpressed specifically from the frg-1 promoter, disrupts the adult ventral muscle structure and organization. Together, these data further support a role for FRG1 overexpression in FSHD pathophysiology and reveal the previously unsuspected direct involvement of FRG-1 in muscle structure and integrity.